Cyberbullying of children: Challenges of victim support - Paunović Nikola (Temida)
Bullying in the form of verbal, physical and social harassment is an integral problem for all societies. With the development of information and communication technology, cyberbullying of children as a new type of bullying increasingly attracts the attention of scholars. Bearing in mind that cyberbullying of children is the subject of this paper, various theoretical approaches, defining this phenomenon, are analyzed. Furthermore, special attention is paid to existing international, European and national legal framework in the context of cyberbullying of children. Finally, starting from the phenomenological forms of cyberbullying of children, the focus is on the challenges of providing victim support. In concluding remarks, it is stated that the lack of a single understanding of cyberbullying of children is a consequence of the absence of a comprehensive legally binding document devoted to this problem. The main goal of the article is to raise awareness about the need to adopt a comprehensive legally binding document devoted to cyberbullying of children in order to protect the rights of victims in cyberspace.